Studi Komparasi Metode Pendidikan Akhlak Menurut Imam Al-Ghazali, Ibnu Miskawaih dan Imam An-Nawawi - Muh. Khoirul Anam (Fahima, 2023)
This research aims to: 1) find out the method of moral education according to Al-Ghazali; 2) find out the method of moral education according to Ibnu Miskawaih; 3) find out the method of moral education according to Imam An-Nawawi; 4) find out the comparison of moral education methods according to Al-Ghazali, Ibn Miskawaih and Imam An-Nawawi. This research is a type of qualitative research with literary research methods or library research. Data comes from primary sources (Ihya' Ulumuddin, Tahdzib al-Akhlak, Riyadhus Shalihin) and secondary sources as well as various available sources including printed books, scientific journals, and the internet. The data analysis technique uses a comparative descriptive method to find out the characteristics of the message which is carried out objectively and systematically related to the moral education method of Al-Ghazali, Ibnu Miskawaih, and Imam An-Nawawi. Which then compares the three research objects so that similarities and differences are obtained. The results of this study indicate that there are similarities and differences in moral education methods according to Al-Ghazali, Ibn Miskawaih, and Imam An-Nawawi. The similarities include the view of changeable morals and the goal of moral education, namely the perfection of life. While the difference lies in the process that goes through in moral development which has advantages and disadvantages to each other.